2020
DOI: 10.1159/000510327
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of FMO3 Variants on Plasma Disposition and Adverse Reactions of Oral Voriconazole in Febrile Neutropenia

Abstract: Background and Objectives: With the increasing number of patients with febrile neutropenia (FN), voriconazole (VRC) has been widely used in hospitals for first-line treatment of FN. The study was designed for evaluating the influence of FMO3 mutation on the plasma disposition and adverse reactions of VRC in FN. Materials and Methods: A single-center observational study was conducted in the inpatient ward for 4 years. The genotypes of FMO3 and cytochrome P450 (CYP) 2C19 were detected by PCR-restriction fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Clinical information was collected and ADRs were recorded in an earlier study ( Wang et al, 2020 ). A 5 ml sodium -heparin tube was used for blood sample collection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical information was collected and ADRs were recorded in an earlier study ( Wang et al, 2020 ). A 5 ml sodium -heparin tube was used for blood sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid LC-MS/MS was conducted as previously described ( Wang et al, 2020 ). A Waters UPLC-TOF-MS (Waters ACQUITY UPLC™ System Tandem Waters LCT Premier XE TOF-MS; Waters Corp., Milford, MA, United States) was usedto determine plasma VRC and VRC N-oxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Park et al (13) and Sung et al (14) demonstrated that the SnPs c.855c>T and c.472G>a affected the pharmacokinetics of sulindac in women who underwent preterm labor. Febrile neutropenia, myelosuppression and agranulocytosis related to these SnPs have also been reported previously (25,29,30). considering the relatively high frequency of FMO3 genetic polymorphisms in the population, the functional defects in FMo3 enzymes associated with these SnPs may have notable clinical implications, such as the variations in drug exposure followed by toxicity or delayed elimination of toxic substances.…”
Section: Discussionmentioning
confidence: 65%
“…FMO3 genetic polymorphisms have been the focus of considerable interest in research; these findings can be applied to various studies on the pharmacokinetics of various medications, including anti-diabetics (e.g., teneligliptin) ( 5 , 6 ), antibiotics (e.g., voriconazole) ( 20 , 25 ) and non-steroidal anti-inflammatory drugs (e.g., sulindac) ( 4 , 13 , 14 ), as well as human diseases, such as cardiovascular disorders ( 2 , 7 ). FMO3 increases plasma trimethylamine N-oxide (TMAO) levels by catalyzing the conversion of trimethylamine (TMA) derived from the gut microbiome ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%